Nucleotide sequence and regulation of expression of the Aspergillus nidulans gdhA gene encoding NADP dependent glutamate dehydrogenase. - Hawkins, A; Gurr, S; Montague, P; Kinghorn, JR (1989)
The nucleotide sequence of the Aspergillus nidulans gdhA gene encoding NADP linked glutamate dehydrogenase has been determined and Northern blot analysis used to study the regulation of expression of this gene. The gdhA gene is 1485 nucleotides long and, by comparison with the corresponding Neurospora crassa am gene, has two putative introns of 53 nucleotides and a protein encoding region of 1380 nucleotides that codes for an inferred protein of 49.63 kDa which shows regions of homology with glutamate dehydrogenase proteins from a range of organisms. mRNA analysis of wild-type mycelium grown under a variety of conditions shows that: (a) the highest levels are seen with glucose as the carbon source with inorganic nitrogen; and (b) no gdhA mRNA is detectable when cells are transferred to amino acids as sole carbon source, closely matching the observed glutamate dehydrogenase activity levels under identical conditions. The results presented strongly suggest that a good carbon source is a prerequisite for transcription, but the molecular mechanism responsible is unclear.